Poetyka w liceum… Zstąpmy na ziemię! - Matusiak, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The article analyses the results of the surveys conducted among teachers and students concerning the scope and the form of the application of poetics in upper secondary schools. It also presents an evaluation of the usefulness of this field of education in school practice, both with regard to the core curriculum and to the examination standards in force during the General Secondary Education Exam in Polish. The article also addresses the questions of the extent to which school teaches poetics for the purpose of good grades at the above-mentioned exam, and the extent of the actual need to discuss the artistic organisation of a literary work with students.
Poetics in High School… High Time to Come Down to Earth!
Keywords: poetyka; analiza dzieła literackiego; szkoła ponadgimnazjalna; standardy egzaminacyjne; matura; podstawa programowa